Remote terminal unit - Mohd Ruddin, Ab Ghani; Mohd Ariff, Mat Hanafiah; Wan Nor Shela Ezwane, Wan Jusoh; Siti Hajar, Raman; Wan Ahmas Redhauddin, Wan Hassan (2014)
According to embodiments of the invention, a Remote Terminal Unit (RTU) (100) for monitoring and controlling safety devices is disclosed. The disclosed RTU (100) have a processor (102) wherein the processor (102) monitors fault operation of the safety device, collects data and periodically communicate the data to a remote control unit using a communication module, performs periodic analyses of the safety device (106) and communicates faulty status of the safety device (106) to the remote control unit.